Assessing the validity and reliability of the Turkish versions of craving beliefs and beliefs about substance use questionnaire in patients with heroin use disorder: demonstrating valid tools to assess cognition-emotion interplay - Melike Küçükkarapınar; Hale Yapici Eser; Vahap Ozan Kotan; Merve Yalcinay-Inan; Rifat Tarhan; Zehra Arikan (BMC, 2018)
Abstract Background Cognitions associated with craving and substance use are important contributors for the psychological theories of Substance use disorders (SUD), as they may affect the course and treatment. In this study, we aimed to validate Turkish version of two major scales 'Beliefs About Substance Use'(BSU) and 'Craving Beliefs Questionnaire'(CBQ) in patients with heroin use disorder and define the interaction of these beliefs with patient profile, depression and anxiety symptoms, with an aim to use these thoughts as targets for treatment. Methods One hundred seventy-six inpatients diagnosed with heroin use disorder and 120 participants in the healthy comparison group were evaluated with CBQ, BSU, Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI) and sociodemographic data questionnaire. Patient group was also evaluated with Addiction Profile Index. Reliability and validity analysis for scales were conducted. Linear regression analysis was conducted to evaluate the determinants of BSU and CBQ scores. Results Cronbach alpha level was 0.93 for BSU and 0.94 for CBQ. Patient group showed significantly higher CBQ, BSU, BAI and BDI scores (p < 0.001). BSU score significantly correlated with API-substance use profile score, API-diagnosis, BAI, BDI and CBQ (p < 0.005), whereas CBQ scores significantly correlated with API-diagnosis, API-impact on life, API-craving, API-total score, BSU, BAI, BDI and amount of cigarette smoking (p < 0.002). Number of previous treatments and age of onset for substance use were not correlated with either BSU or CBQ. BAI and BDI scores significantly predicted BSU score, however only BDI score predicted CBQ score (p < 0.003). Conclusions Craving beliefs were highly correlated with addiction profile. Anxiety and depression are significant modulators for patients' beliefs about substance use and depression is a modulator for craving and maladaptive beliefs, validating emotion-cognition interplay in addiction.